The Effect of Electronic Word-of-mouth Perception on Purchase Intention Mediated by Brand Image - Maulita, Elma Dea; Handayanto, Eko; Lestari, Novi Puji (Universitas Muhammadiyah Malang, 2023)
The purpose of this study was to examine the effect of electronic word-of-mouth on purchase intention, mediated by the brand image of Robucca coffee shop in Malang City. Using a quantitative approach, the population used in this study were Instagram followers @robucca.id, with a total sample of 100 respondents analyzed using path analysis. The research results show that perceptions of e-word-of-mouth have a significant effect on consumer purchase intentions. The perception of electronic word-of-mouth has a significant impact on brand image. Brand image has a large influence on consumer purchase intentions. That is, the better the brand image, the more likely consumers are to buy. Brand image has been proven to be an intervening variable in the relationship between e-word-of-mouth perceptions and consumer intentions to buy. This means that the better the brand image, the greater the perceived impact of electronic word-of-mouth on purchase intention.